Pengaruh Dividend Payout Ratio, Price Earning Ratio dan Asset Growth Terhadap Stock Price Volatility - Rizqi Abdul Aziz; Naufal Sinatria; Selly Puspita Sari; Fitria Fertha Agustina (Journal of Business and Economics Research (JBE), 2026)
The background of this study is based on the fact that global economic uncertainty affects the stability of the capital market; specifically, the tourism sector has suffered losses following the economic recovery, resulting in high stock price volatility. Stock price volatility serves as a key indicator in assessing investment risk, which is influenced by corporate financial information such as the dividend payout ratio, price-to-earnings ratio, and asset growth. This study aims to test and explain the effects of the dividend payout ratio, price-to-earnings ratio, and asset growth on stock price volatility among companies in the tourism sector listed on the Indonesia Stock Exchange for the period 2021–2024. This study employs a quantitative method using secondary data from the financial reports of the tourism sector on the Indonesia Stock Exchange for the 2021–2024 period, with a population of 42 companies and a sample size of 9 companies across 4 observation periods, resulting in 36 samples. The study utilized purposive sampling, and data analysis was conducted using multiple linear regression with SPSS version 27. The results indicate that, when analyzed individually, the dividend payout ratio and asset growth do not have a significant effect on stock price volatility. Conversely, the price-earnings ratio has a positive and significant effect on stock price volatility, making it the most influential fundamental factor in explaining stock price volatility among companies in the tourism sector. When analyzed simultaneously, the dividend payout ratio, price-earnings ratio, and asset growth have a significant effect on stock price volatility. This study provides empirical evidence that corporate fundamental information particularly the price-earnings ratio is more relevant as a signal for investors in responding to stock price changes in the tourism sector during periods of economic recovery. Furthermore, this study expands the application of signaling theory to explain how markets respond to corporate financial information.